Uma análise da polarização de renda no caso brasileiro 1981-2003 - Castro, Sueli Aparecida Corrêa e (2006)
The main objective of this work was to present a measure of income polarization for Brazil, and to apply it for different concepts of domiciliary income for the years of 1981, 1992 and 2003. More specifically, we present the methodology that in allowed to separate them the domiciles in two groups of income, the call bipolarization of income. A general picture of the inequality of income in the last decades, the main differences between a traditional measure of income inequality and a measure of polarization and the methodology was presented to get a measure of polarization. Finally, the analysis of the gotten results was made and a comparison enters the bipolarization found for Brazil and some countries of the OCDE, what it led if to conclude that Brazil relatively presents a high index of polarization to the too much countries, mainly due to great distance enters the average income of the groups. In turn, the measure if practically presented steady in last the 20 years following the trend of the income inequality.